PENGARUH JENIS AGREGAT KASAR TERHADAP KARAKTERISTIK BETON SELF COMPACTING CONCRETE - Restu Sakha Alam; Masagus Taswin (JURNAL ILMIAH BERING'S, 2020)
Concrete is a construction material that cannot be separated with modern social life. Self Compacting Concrete is concrete that can condense under its own weight. The purpose of this study was to determine the effect of coarse aggregate types on the characteristics of Self Compacting Concrete concrete. To find out the Self Compacting Concrete criteria, workability and flowability testing is performed using the EFNARC method. And compressive strength testing using SNI 1974: 2011. Based on the results of tests conducted in the laboratory of the College of Natural Fence Technology. The optimum compressive strength value obtained at 28 days with the code specimen K1 20.06 MPa and K2 15.42 MPa. The effect of coarse aggregate which has a smooth surface can reduce the compressive strength in concrete Self Compacting Concrete.